Imaging of elbow entrapment neuropathies - Domenico Albano; Gabriella Di Rocco; Salvatore Gitto; Francesca Serpi; Stefano Fusco; Paolo Vitali; Massimo Galia; Carmelo Messina; Luca Maria Sconfienza (Insights into Imaging)
Abstract Entrapment neuropathies at the elbow are common in clinical practice and require an accurate diagnosis for effective management. Understanding the imaging characteristics of these conditions is essential for confirming diagnoses and identifying underlying causes. Ultrasound serves as the primary imaging modality for evaluating nerve structure and movement, while MRI is superior for detecting muscle denervation. Plain radiography and CT play a minor role and can be used for the evaluation of bony structures and calcifications/ossifications. Comprehensive knowledge of anatomical landmarks, nerve pathways, and compression sites is crucial for clinicians to accurately interpret imaging and guide appropriate treatment strategies for entrapments of ulnar, median, and radial nerves, and their branches. Critical relevance statement Accurate imaging and anatomical knowledge are essential for diagnosing elbow entrapment neuropathies. Ultrasound is the preferred modality for assessing nerve structure and motion, while MRI excels in detecting muscle denervation and guiding effective management of ulnar, median, and radial nerve entrapments. Key Points Ultrasound is the primary modality for assessing nerve structure and stability. Findings include nerve structural loss, isoechogenicity, thickening, and hyper-vascularization. MRI provides a comprehensive evaluation of the elbow and accurate muscle assessment. Imaging allows the identification of compressive causes, including anatomical variants, masses, or osseous anomalies. Awareness of anatomical landmarks, nerve pathways, and compression sites is essential. Graphical Abstract